Evaluative exploration of inclusive public relations practices for students with disabilities - Silitonga, Arwinda Audiary; Zahro, Siti Aminatus; Pinariya, Janette Maria (Universitas Padjadjaran, 2026)
Background: Existing studies on disability inclusion in higher education have primarily focused on learning support, disability services, and educational accessibility, and limited attention has been given to public relations (PR) as a strategic function in inclusive institutional communication. Furthermore, Excellence Theory, the Preparation–Implementation–Impact (PII) Model, and Inclusive Communication have rarely been integrated into evaluate inclusive PR practices. Purpose: This study explores and evaluates inclusive PR practices for students with disabilities in Indonesian higher education and develops an integrated conceptual model. Methods: Guided by a constructivist paradigm, this qualitative multiple-case study involved eight purposely selected informants from a state university (Universitas Negeri Jakarta) and a private university (LSPR Institute of Communication and Business). Both universities were selected because they provide services for students with disabilities while representing different institutional contexts. Data were collected through semi-structured interviews, observations, and document analysis and analyzed using the interactive model of Miles, Huberman, and Saldaña, supported by NVivo. The PII Model served as the evaluative framework, while Excellence Theory and Inclusive Communication guided data interpretation. Results: Inclusive PR practices are shaped through interactions among PR strategic role, communication implementation, institutional support, students’ communication experiences, and continuous evaluation. Although both universities adopted more participatory and accessible communication, accessibility cannot be determined solely by communication channels or disability support services because barriers differ across disability types. Communication evaluation also remained largely informal, limiting the systematic use of students’ experiences in future planning. Conclusion: This study proposes the Ecosystem-Based Inclusive PR Practices Conceptual Model, which reconceptualizes inclusive public relations as a collaborative, adaptive, and experience-driven communication ecosystem. Implications: The proposed model extends Excellence Theory, the PII Model, and Inclusive Communication by positioning evaluation as a continuous organizational learning mechanism and provides practical guidance for strengthening sustainable inclusive communication in higher education.